Histopathological Study of the Liver in Balb/C Mice with Lupus Treated by Bone Marrow-Derived Mesenchymal Stem Cells (Bm-Mscs) - Ghassan Esmael; Hassan Ulaiwi; Noor Majed; Wijdan abd Al Hussein (Basrah Journal of Veterinary Research)
lupus is an autoimmune disease that occurs in animals and humans, characterized by producing autoimmune antibodies against its cells proteins. The present study investigates the tissues changes of the liver in BALB/c mice with lupus and investigation the effects of bone marrow-derived mesenchymal stem cells (BM-MCSs) for treatment of the tissues pathological changes. The study included forty BALB/c mice, the animals divided into equally four groups. G1 included mice with lupus. G2 included mice with lupus, then treated by BM-MCSs. G3 are administered BM-MCSs alone. G4 administrated PBS. After ending the treatment periods, all the animals were sacrificed. The liver was placed in buffer formalin 10% and sent to the histopathology laboratory to determine the histopathological changes in all study groups. The histopathological changes of G1 are liver severe necrosis with atrophy, hydropic lever cells, very wide sinusoids, severe hemorrhage, and engorged central vein. G2 showed normal lever cells with slight necrosis. G3 and G4 showed normal architecture of the liver tissue. Lupus causes histopathological changes in the mice's liver; MSC can ameliorate and treat the liver's histopathological changes in BLAB/c mice with lupus.